Caffeic Acid Phenethyl Ester Protects Neurons Against Oxidative Stress and Neurodegeneration During Traumatic Brain Injury - Nurul Sulimai; Jason Brown; David Lominadze (Biomolecules)
Traumatic brain injury (TBI) is an inflammatory disease causing neurodegeneration. One of the consequences of inflammation is an elevated blood level of fibrinogen (Fg). Earlier we found that extravasated Fg induced an increased expression of neuronal nuclear factor kappa B (NF-κB) p65. In the present study, we aimed to evaluate the effect of caffeic acid phenethyl ester (CAPE), an inhibitor of NF-κB, on Fg-induced neurodegeneration in vitro and in mice with mild-to-moderate TBI. Primary mouse brain cortical neurons were treated with Fg (0.5 or 1 mg/mL) in the presence or absence of CAPE. A cortical contusion injury -induced model of TBI in C57BL/6 mice was used. Mice were treated with CAPE for two weeks. The generation of reactive oxygen species (ROS) and neuronal viability were assessed. Mice memory was assessed using novel object recognition and contextual fear conditioning tests. The generation of ROS and viability of neurons in vitro and in the brain samples were assessed. Data showed that CAPE attenuated the Fg-induced generation of ROS and neuronal death. CAPE improved the cognitive function of the mice with TBI. The results suggest that Fg-induced generation of ROS could be a mechanism involved in cognitive impairment and that CAPE can offer protection against oxidative damage and neurodegeneration.